Mónica Inés Cejas y Alejandra Galindo Marines, coords. 2022. Mujeres desde el Sur. Poéticas del encuentro con Asia y África . Ciudad de México: Ítaca. 214 pp. ISBN 9786078077533 - Franco Silva, Adriana (El Colegio de México, 2025)
Mónica Inés Cejas y Alejandra Galindo Marines, coords. 2022. Mujeres desde el Sur. Poéticas del encuentro con Asia y África. Ciudad de México: Ítaca. 214 pp. ISBN 9786078077533